The diagnostic and prognostic role of proteomics and metabolomics in Polycystic Ovary Syndrome - Khan, Gulafshana H. (2018)
Polycystic ovarian syndrome (PCOS) is a common endocrine disorder, affecting up to 10% -26% of women of reproductive age. Diagnostic criteria is somewhat controversial but ever evolving.